(untitled) (SAARC Journal of Agriculture, 2018)
The study was conducted to know the reproductive performance of spiralling whitefly on guava. Number of colony, eggs, 1st instar, 2nd instar, 3rd instar and 4th instar nymphs per five leaves ranged from 6 to 15, 8 to 32, 0 to 44, 0 to 22, 0 to 45 and 0 to 28, respectively. Maximum number of adults and nymphs were found in the month of January. Highest longevity of Aleurodicus dispersus (21.5 days) was recorded in adult while the lowest was in 2nd instar nymph (6.4 days). The number of colony/leaf and number of 3rd and 4th instar nymphs of A. dispersus had significant positive correlation with minimum and maximum temperature while non-significant positive correlation is observed between the number of egg/colony, the number 1st and 2nd instar nymphs with minimum and maximum temperature. A. dispersus showed nonsignificant positive correlation with minimum and maximum relative humidity regarding number of colony/leaf, 2nd instar nymph while nonsignificant negative correlation with 4th instar nymph. SAARC J. Agri., 15(2): 207-214 (2017)